The Rescuers. - Walt Disney Productions (New York : Random House, 1977)
Two enterprising mice live up to the motto of the Rescue Aid Society, "We help anyone ... anywhere," when they rescue a kidnapped orphan.
Based on a full-length animated film of the same title.
Keywords: Mice; Kidnapping